Effect of Nitrate on the Organic Acid and Amino Acid Composition of Legume Nodules - Streeter, John G. (1987)
Nitrate supplied to legume plants inhibits the activity of nitrogenase in Rhizobium bacteroids in root nodules. The accumulation of amino N which is known to occur in Glycine max (L.) Merr. nodules as nitrogenase activity declines was studied in more detail by analysis of changes in free amino acid composition in response to high nitrate supply. A 6-fold increase in asparagine concentration in Bradyrhizobium japonicum bacteroids was found about the time of maximum nitrogenase inhibition. However, the accumulation of amino acids in soybean nodules lagged behind the inhibition of nitrogenase. Furthermore, in studies of a second legume, Phaseolus vulgaris (L.) inoculated with two different strains of Rhizobium phaseoli, a high nitrate treatment inhibited nitrogenase but had no significant effect on amino acid composition of nodules. The possibility that nitrate may interfere with the supply of carbon substrates to bacteroids was examined by the analysis of organic acids in legume nodules supplied with nitrate. Nitrate had a small (10-20%) negative effect on the concentration of tricarboxylic acid cycle acids in P. vulgaris nodules. However, in G. max nodules, high nitrate treatment resulted in significant increases in the concentration of malate, succinate, fumarate, and citrate. Thus, carbon deprivation of bacteroids also seems unlikely as a cause of the inhibition of nitrogenase by nitrate. There was a transient increase in ammonium concentration in P. vulgaris nodules in response to high nitrate treatment. This effect was rapid relative to other effects of nitrate on nodule composition and was roughly coincident with the rapid decline in acetylene reduction activity.